Reinterpretation of Gender Values in Islam: A Critical Study from a Contemporary Feminist Perspective - Maknun, Luluil; Zakaria, Muhammad Fadhlurrahman (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Reinterpretation of gender values in Islam has the potential to continue to shine and develop more widely to uphold gender equality despite the many challenges that must be faced. The purpose of this study is to find out in detail about the reinterpretation and interpretation of gender values in Islam based on religious texts such as the Qur'an and Hadith, to find out how the relationship between gender values from the perspective of Islamic feminism and the perspective of contemporary feminism, and to find out the challenges and solutions that Islamic feminism must do in fighting for Islamic gender values so that they continue to shine on the world stage. The method used in this article is descriptive-analytical using a comparative theory between Islamic feminist theory and contemporary feminism. And in this article the researcher reveals several findings including: Muslim feminists argue that many traditional interpretations do not fully reflect the original message of the Qur'an, especially regarding gender equality issues. Therefore, a deeper interpretation of religious texts that discuss these issues must be carried out. However, a significant challenge comes from conservative resistance in the Muslim community, who consider this approach a threat to Islamic teachings and culture. This research is very important to be reviewed in depth because the urgency of this research must be disseminated so that many people know the struggle of Islamic feminism to raise Islamic gender values in the modern era.